The incidence rate of caries on individual tooth surfaces and its distribution by age and gender in clinic patients of Hawler Medical University/College of Dentistry: a retrospective cross-sectional study. - Niaz Hamaghareeb Hamasaeed; Eman Kanabi Mohammed; Kazhin Mahmood Omer; Rayan Amir Bapir (Erbil Dental Journal, 2023)
Background and objectives: Dental caries is one of the most prevalent chronic diseases, which is caused by cariogenic oral bacteria. This study is aimed to realize the distribution of caries on individual permanent tooth surfaces, and compares these results among various age groups and gender.